Purificação e caracterização parcial de uma lectina lactose-específica com ação pro-inflamatória de sementes de dioclea reflexa - Lóssio, Cláudia Figueirêdo (2016)
Lectins with lactose binding specificity isolated from seeds of phylogenetically close plant species of Diocleinae sub-tribe present different characteristics when compared to the extensively studied mannose/glucose-specific lectins. In this study, a new lactose-specific lectin from Dioclea reflexa seeds (DrfL II) was isolated by a two-step chromatography in Sephadex® G-50 and lactose-Sepharose columns. The SDS-PAGE showed that the pure lectin is composed of a single band, slightly lower than 30 kDa, presenting a different profile from ConA-like mannose/glucose specific lectins. Partial sequence of the protein was obtained by electrospray ionization mass spectrometry covering 30% of the total sequence. DrfL II presented sugar specificity to α-lactose, and high stability at wide range of pH. DrfL II showed no toxicity against Artemia nauplii and induced acute inflammation (paw edema and hipernociception) in mice with the participation of the lectin domain and nitric oxide. Thus, it is important to further determine the complete sequence and tridimensional structure of this new type of lactose-binding lectin in order to be able to compare it with mannose/glucose lectins and their biotechnological applications.